Do small bank deposits run more than large ones? Three event studies of contagion and financial inclusion - Canlas, Dante B.; Ravalo, Johnny Noe E.; Remolona, Eli M. (Journal of Financial Stability, 2025)
How susceptible to contagion are bank deposits associated with financial inclusion? To assess this susceptibility, we analyze the behavior of deposits around three significant events of bank failure in the Philippines. We conduct the event studies with the advantage of a unique dataset that disaggregates deposits by size at the town level. We show that both small and large deposits are withdrawn up to 4–5 quarters before the bank’s closure. We take advantage of this distinction between small and large deposits to test for contagion. Applying difference-in-difference regressions, we find evidence of contagion: the closure of a large bank leads to withdrawals at banks in neighboring towns by depositors both large and small. This is the case for two of the three events, and when the data is taken collectively. That there is a market for information affects deposit insurance as a safety net for depositors and as a disciplining tool for banks. There are also liquidity considerations that banks need to consider. In any case, we consistently find the behavior of small depositors to be no different from that of large depositors. Hence, if financial inclusion is about access to bank deposits, it is not likely to heighten systemic risks nor mitigate them.